2014
DOI: 10.14202/vetworld.2014.398-402
|View full text |Cite
|
Sign up to set email alerts
|

Various dietary levels of protein and energy interaction on growth performance of white plumage japanese quails

Abstract: The present study was investigated to determine the optimum energy and protein requirement for growth performance and nutrient digestibility of white plumage Japanese quail during starter (1 to 3 week) and finisher (4 to 5 week) phases.: Japanese quails were fed with nine diets consisting of three levels of energy (2600, 2800 and 3000; 2800, 2900 and 3000 Kcal ME/kg) and protein (23, 25 and 27;18, 20 and 22% CP) during starter and finisher phases, respectively, in 3×3 factorial design.Protein and energy indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…However, Dowarah & Sethi (13) observed that the growth performance was higher in Japanese quail during starter (1 to 3 week) fed on high protein and high energy (27% CP and 3000 Kcal ME/kg). Jordão Filho et al (3) observed that dietary requirement for protein gain was 30% higher for Japanese quails compared with the European, due to their being less efficient in the use of dietary protein to gain than European quails.…”
Section: Resultsmentioning
confidence: 97%
“…However, Dowarah & Sethi (13) observed that the growth performance was higher in Japanese quail during starter (1 to 3 week) fed on high protein and high energy (27% CP and 3000 Kcal ME/kg). Jordão Filho et al (3) observed that dietary requirement for protein gain was 30% higher for Japanese quails compared with the European, due to their being less efficient in the use of dietary protein to gain than European quails.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies with quails or broiler chickens have shown that performance is adversely affected with low dietary CP and investigated the main reasons for decreasing growth performance (Folorunso, Adesua, & Onibi, ; Malomo, Bolu, & Olutade, ). On the other hand, Dowarah and Sethi () concluded that dietary CP during starter (23%, 25% and 27%) and finisher (18%, 20% and 22%) phases had no influence on performance of Japanese quail. Low‐CP diet supplemented with synthetic amino acids supports quail performance and is an excellent strategy for mitigating ammonia pollution and reducing feeding cost (Alagawany, Abd El‐Hack, Laudadio, & Tufarelli, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many domestic chickens are severely affected by natural heat stress due to location of tropical or subtropical regions [6,9]. Recently, nutritional strategies have been proposed that can be used to improve the tolerance of birds to heat stress, such as dietary reduction of protein [10,11] or energy and the introduction of dietary supplements [12,13]. With the focus on the animal health, more and morenatural and safe feed additives have become the primary choice for farms.…”
mentioning
confidence: 99%